Analysis of risk factors for gestational hypertension and preeclampsia: Literature review - Hayati, Thursina Vera; Zulkarnain, M.; Flora, Rostika; Fajar, Nur Alam; Rahmiwati, Anita; Ocktariyana, Ocktariyana; Ariana, Rika (Science Midwifery, 2024)
Based on Disability Adjusted Life Years (DALYs), there are four main disease burdens, namely ischemic heart disease, cerebrovascular disease (including stroke and hypertension), diabetes and tuberculosis infectious disease. Gestational hypertension is very closely related to CVD (cardiovascular disease) with the potential for preeclampsia to have an impact on premature birth or small babies for the gestational age, stillbirths, low birth weight babies, etc. The research objective was to analyze the risk factors for gestational hypertension and preeclampsia. Methods: This study is a literature review based on the PRISMA guidelines. using electronic databases namely Google scholar, Sciencedirect and Pubmed with a period from 2017 to 2022 with the keywords "Hypertension, risk factors, high risk pregnancy". Results: The prevalence of hypertension and pre-eclampsia varies between countries. In Bangladesh, the prevalence of pre-eclampsia: 14.4%, without history of hypertension, 5.4% prevalence of pre-eclampsia with chronic hypertension, the same as Ethiopia. The incidence of gestational hypertension is 6%, in Ireland, gestational hypertension is 5.9% and 4.6% of pre-eclampsia. In France hypertension was 7.4% and pre-eclampsia was 2.0%, gestational hypertension was 4.2%, HELLP syndrome was 10.4%. Hypertension is associated with risk factors for pregnancy, lifestyle and sociodemographic factors. Conclusion: Prevention, timely diagnosis and prompt management of hypertension in pregnancy should be intensified so as to reduce morbidity and severity of adverse birth outcomes